Microstructures, Mineral Compositions, and Mechanical Properties of Red-Layers in Southern China - Huizhi Zhang; Jifeng Liu (Advances in Materials Science and Engineering)
In order to reveal the water-induced damage mechanism and mechanical properties of red-layers in Southern China, typical red-layer samples are experimentally studied by scanning electron microscope (SEM), energy spectrum analysis, XRD, and mechanical tests. The results show that some red-layer samples contain a large number of smectite and illite-smectite mixed-layer clay minerals and their microstructures are mainly stacked microaggregates in which mutual agglomeration is formed by flake and tabular clay particles. Widespread distribution micropores and fractures in microaggregates provide the necessary moisture migration channels. The various cemented materials produce a kind of irreversible structural strength, and this strength is vulnerable for the aqueous medium conditions. The influence of microstructures and mineral compositions on red-layer mechanical properties is discussed. The results could provide the reference for further research about the water-induced damage mechanism of red-layers in Southern China.